Influence of the groove shape on welding residual stresses in P92/SUS304 dissimilar metal butt-welded joints. (June 2021) - Li, Suo; Hu, Long; Dai, Peiyuan; Bi, Tao; Deng, Dean
Abstract: Two dissimilar metal butt-welded joints between P92 steel and SUS304 stainless steel were fabricated with different groove shape, namely single V-groove and X-groove, by gas tungsten arc welding process. Based on Sysweld software, three-dimensional thermal-metallurgical-mechanical coupled finite element analyses were performed to investigate the welding-induced residual stresses in P92/SUS304 dissimilar metal butt-welded joints. Meanwhile, the hole-drilling strain gauge method was used to measure the distributions of residual stresses on the top and bottom surfaces of the two butt-welded joints. The results obtained indicate that the predicted welding residual stresses achieve good levels of agreement with the measurements. In the numerical model, the solid-state phase transformation in P92 steel, the strain hardening and annealing effect in SUS304 stainless steel, and the discrepancy in thermal expansion coefficients between dissimilar metals were carefully considered. The simulated results show that these three factors have significant influence on the formation of longitudinal residual stresses in P92/SUS304 butt-welded joints. In addition, the distribution of welding residual stresses in the butt-welded joint with X-groove was compared with that in the joint with single V-groove. The results suggest that the butt-welded joint with X-groove may be superior to that with single V-groove in reducing the region of high tensile residual stress.